Aplikasi Absensi Pegawai Berbasis Website : Studi Kasus : Kantor Wali Nagari Siguntur - Ade Triawan; Vella Elka Putri; April Zahmi (Ekasakti Jurnal Penelitian dan Pengabdian, 2025)
The manual attendance process still used at the Wali Nagari Siguntur Office causes several issues, such as reporting delays, potential data manipulation, and difficulties in monitoring employee attendance. To address these problems, this study aims to design and develop a web-based employee attendance application that supports more effective and efficient attendance recording and leave requests. This research adopts a descriptive qualitative approach with a system development model, which includes stages of needs analysis, design, implementation, and testing. The system was tested using the black box method to ensure all application features function properly. The test results show that the system performs well, covering features such as multi-user login, check-in and check-out recording, leave submission, and report generation. The implementation of this application significantly improves the efficiency of attendance management, reduces potential errors, and facilitates real-time monitoring of employee presence.